INDONESIA’S POLICY ON THE LAND BORDER AREA MANAGEMENT WITH MALAYSIA (An Evaluative Study in the Entikong District) - Sandy Nur Ikfal Raharjo (Widyariset, 2013)
ndonesian government has implemented new paradigm on the land border area management by combining security and prosperity approaches. This Evaluative research compared Entikong border area condition in West Kalimantan when the combined-approach based policy is implemented, with the condition before. The result showed that this policy is potensial to solve infrastructure weakness, trade dependence on Malaysia, poor education, threat to nationalism, and lack of coordination among institutions. But, this combined approach also proved lack of attention toward socio-culture aspect in local community. This research recommends Indonesian government to ask for active society involvement in decision making process and implementation of the policy on the land border area management. Thus, the objectives of security, prosperity, and socio-culture will be reached together.